Raoultella ornithinolytica Infection in the Pediatric Population: A Retrospective Study - Pi, Dan-dan; Zhou, Fang; Bai, Ke; Liu, Chengjun; Xu, Feng; Li, Jing (Frontiers in Pediatrics, 2020)
Raoultella ornithinolytica is a pathogen causing an increasing number of pediatric infections. The objective of this study was to investigate the clinical characteristics of R. ornithinolytica infections in children. As a retrospective analysis, clinical features and drug susceptibility data of the five cases were analyzed and related literature was reviewed. A total of 14 cases (eight females, six males) were analyzed: nine cases were retrieved from PubMed, Web of Science, and three domestic databases; five cases occurred in our hospital. The primary diseases of the older children were mainly of neoplastic and immune origin, while cases of infants and young children were mostly complicated by congenital malformation. Fever was the main symptom, and neonatal infection was mainly manifested by dyspnea and hypoxemia, with multiple skin flushes, systemic erythema, and leukocytosis. Of the 14 cases, six were ventilator-assisted, five had indwelling urethral catheters, three had surgical treatment or chemotherapy, and one had multiple rounds of continuous renal replacement therapy (CRRT). Blood infection is the main route of R. ornithinolytica infection in children. Skin flushing and systemic erythema might be positive clues for newborn infection. Patients with multiple congenital abnormalities are susceptible to infection. Tumors, immune deficiency, and invasive operations increase the risk of infection. Blood culture was the main method of disease identification. Blood culture was the main method of disease identification. Based on the drug susceptibility results, the preferred antibiotics are third generations of cephalosporins, carbapenems, quinolone, and aminoglycoside. Lastly, patients with sepsis mostly have poor prognosis.